Study of the effects of operating factors on the resulting producer gas of oil palm fronds gasification with a single throat downdraft gasifier - Guangul, F.M. (Elsevier Ltd, 2014)
Malaysia has abundant but underutilized oil palm fronds. Although the gasification of biomass using preheated inlet air as a gasifying medium is considered an efficient and environmentally friendly method, previous studies were limited to certain types of biomass wastes and gasifier designs. Hence, the effects of preheating the gasifying air on oil palm fronds gasification in a single throat downdraft gasifier are presented in this paper. In addition, the effects of varying the flow rate of the gasifying air and the moisture content of the feedstock on the outputs of oil palm fronds gasification were studied. A response surface methodology was used for the design of the experiment and the analysis of the results. The results showed that preheating the gasifying air to 500 Â°C increased the concentrations of CO from 22.49 to 24.98, that of CH4 from 1.98 to 2.87, and that of H2 from 9.67 to 13.58 on dry basis in the producer gas at a 10 feedstock moisture content. Conversely, the dry basis concentrations of CO, CH4, and H2 decreased from 22.49, 1.98 and 9.67 to 12.01, 1.44 and 5.45, respectively, as the moisture content increased from 10 to 20. The airflow rate was also proven to significantly affect the quality of the resulting producer gas. Â© 2014 Elsevier Ltd.